Pemanfaatan Limbah Magnet sebagai Sumber Energi Listrik pada Lampu LED dan Charger Handphone - Yusia Edvin Anjasmara; Iswanto Iswanto; Bambang Suwerda (Poltekkes Kemenkes Yogyakarta, 2020)
Because of its characteristics, magnet has important role in supporting the functioning of electronicdevices. However, abandoned magnet or magnet waste has potential harm for environmentand human. The purpose of this study was to reduce the accumulation of magnet waste and utilizeit as a source of electrical energy, by means of rotating the pedal of in the created tools, andthen the energy is then delivered to anchor component and then to capacitor. The study was apre-experiment with post test only design, where the electrical energy was used to LED lampand to charge mobile phone. The results showed that the power plant can turn on LED lights for15 minutes, and can charge mo-bile phone, i.e. in 5 minutes obtained 2% battery increase, in 10minutes 4% increase, and in 15 minutes 6% increase. It can be concluded that the created powergeneration equipment can be a solution to reduce magnet waste accumulation, and as thesource of electrical energy.